Fulfilling Children's Nutritional Rights: An Islamic Family Law Analysis of Indonesia's Free Meal Program - Muh Abdullah Rizal; Hannani; Syafaat Anugrah Pradana; Rusdaya Basri; Muh. Nurhidayat (Journal of Family Law and Islamic Court, 2026)
This article examines state responsibility in fulfilling children's nutritional rights through the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) from the perspective of Islamic family law in Sidenreng Rappang Regency. The study departs from the dual structure of responsibility in meeting children's basic needs: Islamic law assigns primary responsibility for child maintenance (nafkah anak) to parents, particularly the father, while the state is constitutionally and socially obliged to protect public welfare. This research aims to analyse the legal position of the MBG Program within the framework of Islamic family law and to explain the form of synergy between parental obligations and state intervention. The study uses a normative-empirical approach with a descriptive-analytical qualitative design. Normative data were obtained from Islamic legal sources, statutory regulations, and relevant literature, while empirical data were collected through semi-structured interviews, field observation, and documentation involving family, school, health, program-management, and local-policy actors. The findings indicate that the MBG Program does not replace parental maintenance obligations; rather, it complements and strengthens family capacity in meeting children's nutritional needs. The program also contributes to children's health, learning readiness, and school participation. The study concludes that the relationship between parental responsibility and state intervention is complementary, not substitutive. This synergy reflects the principles of maqasid al-shari'ah, maslahah, and social solidarity (takaful ijtima'i), thereby positioning public policy as a form of contemporary ijtihad aimed at advancing social welfare.